Switching and imaging of magnetic structures in iron oxides - Chen, J (2022)
Spintronics is a multidisciplinary science aiming to develop the next-generation electronic device at the age when Moore’s Law has met its limit. Magnetic oxides, as a traditional material widely applied in CMOS and memory devices, have attracted tremendous attention in spintronics because of many important compounds such as multiferroics and antiferromagnets; both are dominant platforms for studying strong correlation physics. In this thesis, I look at a new type of multiferroic single crystal Ba0.5Sr1.5Mg2Fe12O22 and a time-honoured antiferromagnet α-Fe2O3 thin film. I investigate the magnetic domains and the coupling between different magnetic orders for multiferroic candidates. As for the antiferromagnets, I developed a state-of-art imaging technique for probing antiferromagnetic domains, and a series of topological structures were discovered to profit from this technique.